COMPARISON OF EFFICACY AND SAFETY OF RANOLAZINE AND IVABRADINE IN CHRONIC ISCHEMIC HEART DISEASE PATIENTS - Ahsan Waqas Khan Niazi; Ahsan Nisar; Syed Naveed Pirzada; Naveed Yaqoob; Muhammad Naeem; Hafsa Shahid Malik; Muhammad Faisal Bacha (Journal of Ayub Medical College Abbottabad, 2024)
Background: Ischemic heart disease (IHD) frequently produces persistent angina that may significantly impair quality of life despite standard treatment. There is need for effective adjunctive therapies to manage refractory angina. Ranolazine and Ivabradine are two potential options that have shown efficacy in alleviating angina symptoms and improving quality of life in IHD patients. Methods: Ethical clearance was obtained from hospital ethical committee before initiation of study. Those patients fulfilling study inclusion criteria were enrolled. Written informed consent was obtained from all the patients. This randomized clinical trial enrolled patients from the Department of Cardiology, PIMS Hospital, Islamabad. The information regarding demographic and baseline patient characteristics were recorded. Patients were randomly assigned into two groups by lottery method. Treatment group (group A) was Ranolazine 500 mg tablets twice daily for 8 weeks plus standard treatment while the Placebo group (group B) was Ivabradine 5 mg tablets twice daily for 8 weeks plus standard treatment. The primary outcome of study was improvement in angina as assessed by SAQ. Other outcomes like hemodynamic stability (heart rate and Blood pressure) and associated side effects were also recorded at 2, 4, 6, and 8 weeks after the start of treatment in both the study groups. The collected data was analyzed by using SPSS 23 version. Results: The mean age of patients in Group A was 64.59±5.47 years and in Group B were 65.41±5.95 years. In Group A 36(78.3%) patients were male and 10(21.7%) patients were female and in Group B 38(82.6%) patients were male and 8(17.4%) patients were female. The baseline score of SAQ in Group A and Group B was as (41.93±4.23 vs 43.24±4.44) and at 8 week as (90.98±3.12 vs 81.48±2.52). Ranolazine had better clinical outcome than Ivabradine for the treatment of persistent angina in patients with chronic stable ischemic heart disease in terms of SAQ score, systolic & diastolic blood pressure and safety profile. Conclusion: This study concluded that Ranolazine in comparison to Ivabradine has better clinical outcomes in terms of efficacy & safety in patients with chronic IHD who had persistent symptoms.